The genome sequence of the variegated scallop, Mimachlamys varia (Linnaeus, 1758) [version 1; peer review: 2 approved, 1 approved with reservations] - Mary E. Spencer Jones; Chris Fletcher (Wellcome Open Research, 2023)
We present a genome assembly from an individual Mimachlamys varia (the variegated scallop; Mollusca; Bivalvia; Pectinida; Pectinidae). The genome sequence is 975.4 megabases in span. Most of the assembly is scaffolded into 19 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 21.78 kilobases in length.